ROLE OF MITOCHONDRIAL DNA ANALYSES IN PROVENANCING UNKNOWN HUMAN SKELETAL REMAINS: PROBABILITIES AND LIMITATIONS (Journal of Forensic Medicine & Toxicology, 2021)
Ancient degraded remains of human origin can beidentified using ancient DNA analyses. The mitochondrialDNA is a useful tool to solve unsolved cases in relation toidentification of an individual where nuclear DNA is toodegraded or insufficient to be used for the purpose.Comparative analysis of mtDNA content in petrous boneand the tooth-root cementum have revealed that later isbest substrate for studying genomic analyses of ancienthuman populations The dental DNA is less prone tocontamination, and the preservation of ancient DNA fromdental samples is easier than bones. The selection ofcorrect decontamination method, appropriate extractionprotocol provides best results and thus increases value ofbones and teeth as a forensic evidence in cases whereidentity establishment is problematic. In this reviewarticle, the current status of the methods used in ancientDNA research, the advantages and the limitations of thisarchaeogenetical method have been presented.
Keywords: Mitrochondrial DNA; DNA profiling; unknown identification